2013
DOI: 10.1080/00380768.2013.775004
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of soil microbial communities in response to tillage and crop residue retention in an eroded Loess soil

Abstract: This study reports the effects of a long-term tillage and crop residue experiment on the soil microbial ecology of a Loess soil located in Gansu Province, western China. Tillage and residue management treatments were imposed on a nine-year continuous rotation of maize (Zea mays L. cv Zhongdan No. 2), winter wheat (Triticum aestivum L. cv Xifeng No. 24) and soybean (Glycine max L. cv Fengshou No. 12). After nine years, there were significant effects on topsoil (0-10 cm) carbon, nitrogen, microbial activity, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…In environments with sufficient moisture, residue could promote higher rates of seed decay. The increased micro-flora activity and biomass under residue (Doran, 1980;Govaerts et al, 2007;Yang et al, 2013) would seem to encourage higher rates of seed losses under residue due to decay (Derksen et al, 1996;Kennedy and Kremer, 1996;Chee-Sanford et al, 2006). This hypothesis has had little field testing, but one study found no difference in percent seed decay in exposed versus residue protected soil (Gallandt et al, 2004), indicating the effects may be more complicated and could involve nutrient status and seed coat characteristics (Davis, 2009).…”
Section: Weed Seed Predation Pathogen Attack and Viabilitymentioning
confidence: 87%
“…In environments with sufficient moisture, residue could promote higher rates of seed decay. The increased micro-flora activity and biomass under residue (Doran, 1980;Govaerts et al, 2007;Yang et al, 2013) would seem to encourage higher rates of seed losses under residue due to decay (Derksen et al, 1996;Kennedy and Kremer, 1996;Chee-Sanford et al, 2006). This hypothesis has had little field testing, but one study found no difference in percent seed decay in exposed versus residue protected soil (Gallandt et al, 2004), indicating the effects may be more complicated and could involve nutrient status and seed coat characteristics (Davis, 2009).…”
Section: Weed Seed Predation Pathogen Attack and Viabilitymentioning
confidence: 87%
“…In 2011, common vetch replaced soybean in the crop sequence. Agronomic practices such as seeding and fertilization, were conducted following the recommendations of provincial standard (Yang et al, 2013). During the period 2001-2012, weed control was mainly by hand-cutting.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, problems of weed control under these practices have restricted the application of these combined practices. Crop rotations that include winter wheat (Triticum aestivum L.) and some legume species are widely used in this rainfed area (i.e., Loess Plateau) to improve soil fertility as a result of enhanced content of soil organic matter, nitrogen and phosphorus (Liu et al, 2000;Wang et al, 2006;Yang et al, 2011), increased diversity and activity of soil microorganisms (Yang et al, 2013) and improved soil water content (Shen et al, 2009). This type of rotation is also important in livestock husbandry, for the provision of forage (Li et al, 2002;Ren, 2002;Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects on soil health, such as increased soil carbon reserve and soil microbial diversity, were consistently observed from previous research. Yang et al (2013 a , b ) found that NTS significantly enhanced soil microbial metabolic capacity, compared with no tillage, within the same field. Therefore, NTS has the potential to improve soil fertility and improve agricultural sustainability.…”
Section: Discussionmentioning
confidence: 98%